Pengaruh Sistem Informasi Akademik Berbasis Online Terhadap Kualitas Pelayanan Kartu Rencana Studi di Universitas Negeri Manado - Mewengkang, Ressy (Tumoutou Social Science Journal, 2024)
The purpose of the study was to the effect of the implementation of the academic information system on the quality of academic services for online Study Plan Card Services at the Faculty of Engineering, Universitas Negeri Manado, and to determine the effect of academic information system variables on the quality of academic services. The research method used uses a combination of quantitative and qualitative. The results showed that the academic information system at the Faculty of Engineering, Universitas Negeri Manado with a web-based system that can be accessed through the faculty counter or online. From the results of processing and analyzing questionnaire data, it was found that the academic information system variable had a significant effect on the quality of academic services at the Faculty of Engineering, Universitas Negeri Manado. This can be seen from the T test, which is by comparing the t-table and t-count with a = 5%. The result is that there is a significant influence between the academic information system and the quality of academic services, with t-count (3.833) greater than t-table (1.669). This means that the better the academic information system, the quality of academic services will increase.